Colloidal Gold Based Dipstick Strip For Detection Of Genetically Modified Crops And Produce - RAJESH KUMAR; RAJESHWAR P. SINHA (International Journal of Pharma and Bio Sciences, 2011)
The production of genetically modified (GM) crops is rapidly increasing every single year worldwide. The safety and quality evaluation of these crops is an important issue regarding to consumers’ health. This led the regulatory authorities to implement a set of very strict procedures for the approval to grow and utilize GM produce. Therefore, for fulfilling regulatory compliance on GM labeling and identification of genetic traits, it generated a demand for analytical methods capable of detecting either transgenic DNA introduced or the protein expressed in GM crops. The detection methods include either DNA based PCR assay or protein based ELISA and dipstick assays. This article illustrates the advances in colloidal gold based dipstick procedure for visual discrimination of GM crops/produce from non-GM.